2020
DOI: 10.3389/fchem.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent and Colorimetric Chemosensor for Hg2+ Based on Rhodamine 6G With a Two-Step Reaction Mechanism

Abstract: A fluorescent and colorimetric chemosensor L based on rhodamine 6G was designed, synthesized, and characterized. Based on a two-step reaction, the chemosensor L effectively recognized Hg 2+ . The interaction between the chemosensor and Hg 2+ was confirmed by ultraviolet-visible spectrophotometry, fluorescence spectroscopy, electrospray ionization-mass spectrometry, Fourier-transform infrared spectroscopy, and frontier molecular orbital calculations. The chemosensor L was also incorporated into test strips and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Porphyrin-based chemosensors have been reported for cyanide (Xu et al, 2010 ), fluoride (Kubo et al, 2003 ), nitrite (Yang et al, 2014 ), azide (Zhang et al, 2012 ), chloride (Zhang et al, 2005 ), and phosphate anions (Rodrigues et al, 2014 ). Similarly, metal cations that have been detected using porphyrin chemosensors include zinc(II) (Zhang et al, 2007 ), nickel(II) (Malinski et al, 1990 ), mercury(II) (Zhang et al, 2002 ; Bai et al, 2020 ), iron(III) (Vlascici et al, 2012 ), copper(II) (Gupta et al, 2006 ), lead(II) (Bozkurt et al, 2009 ), and so on. Our research group has already reported sensors based on porphyrin analogs for cyanide ions, fluoride ions, and picric acid (Chahal and Sankar, 2017 ; Dar and Sankar, 2017 ; Rathi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrin-based chemosensors have been reported for cyanide (Xu et al, 2010 ), fluoride (Kubo et al, 2003 ), nitrite (Yang et al, 2014 ), azide (Zhang et al, 2012 ), chloride (Zhang et al, 2005 ), and phosphate anions (Rodrigues et al, 2014 ). Similarly, metal cations that have been detected using porphyrin chemosensors include zinc(II) (Zhang et al, 2007 ), nickel(II) (Malinski et al, 1990 ), mercury(II) (Zhang et al, 2002 ; Bai et al, 2020 ), iron(III) (Vlascici et al, 2012 ), copper(II) (Gupta et al, 2006 ), lead(II) (Bozkurt et al, 2009 ), and so on. Our research group has already reported sensors based on porphyrin analogs for cyanide ions, fluoride ions, and picric acid (Chahal and Sankar, 2017 ; Dar and Sankar, 2017 ; Rathi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the reported methods, N-(rhodamine 6G) lactam-ethylenediamine (A) was synthesized and purified by recrystallization from ethanol. 43 Then, A (460 mg, 1 mmol) and hippuric acid B (180 mg, 1 mmol) were dissolved in methylene chloride (25 mL) and also 4-dimethylaminopyridine (DMAP, 122 mg, 1 mmol) was added as a catalyst. The mixture was reacted at room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…These methods focus on the design and synthesis of coordination ligand-contained fluorophores and the binding process for metal ions sensing in solution. Fluorescent sensors for Hg 2+ , Cu 2+ , Zn 2+ , Cd 2+ , Fe 3+ , Ni 2+ , Cd 2+ , and Cr 2+ are developed by conjunction with suitable probes containing the core fluorophores, such as rhodamine, pyrene, anthracene, naphthalimide, aminoquioline, bithiophene, and coumarin (Saleem et al, 2017 ; Sivaraman et al, 2018 ; Bai et al, 2019 , 2020 ).…”
Section: Fluorescent Molecules For Heavy Metal Ions Detectionmentioning
confidence: 99%